Effectiveness of hand Washing Training Based on Kirkpatrick Theory Level I and II on Nurses - Damayanti, Vinna Amalia; Ernawaty, Ernawaty (Journal of Health Management Research, 2022)
Background: Hospitals have an obligation to provide education and training to staff who are potentially exposed and have direct contact with patients. This research was conducted because the number of handwashing non-compliance in 2017 was still above the standard set by hospital at 0%. Aims: To analyze the elements of hand washing training on nurses based on the training effectiveness by Kirkpatrick’s 2- Level theory. Methods: This research was descriptive, using a questionnaire to know the effectiveness of the training and knowledge. The sample consisted of the nurses at DKT Gubeng Pojok Hospital Surabaya. The sampling technique was total sampling with 14 nurses who participated in the training and also 20 nurses who did not participate. Results: Level 1-reaction starting from the time of training implementation to the classification of trainers get effective results. Level 2-learning got good results on the level of knowledge and ability to remember the material, nurses who took part in the training with scores of 78.57 and 79.29, while for nurses who did not take part in the training with scores of 71 and 64. Conclusion: The level 1-reaction and level 2-learning get effective results. Researchers provide suggestions for hospitals to be able to provide some other training needed by hospital employees.